2023
DOI: 10.1007/s15010-023-02115-7
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and oral–gut microbiome: clinical implications

Maged T. Elghannam,
Moataz H. Hassanien,
Yosry A. Ameen
et al.

Abstract: More than half of the world’s population are colonized with H. pylori; however, the prevalence varies geographically with the highest incidence in Africa. H. pylori is probably a commensal organism that has been associated with the development of gastritis, ulcers, and gastric cancer. H. pylori alone is most probably not enough for the development of gastric carcinoma, but evidence for its association with the disease is high and has, therefore, been classified by the International Agency for Research on Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 148 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…In various years, one can find isolated works in the literature that indicate the need to supplement classical antibacterial therapy in eradication regimens with probiotics containing Lactobacillus acidophilus in order to increase the degree of eradication and reduce the incidence of side effects [45][46][47][48]. It is also shown that Lactobacillus acidophilus had an inhibitory effect on Hp in peptic ulcer patients and also in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In various years, one can find isolated works in the literature that indicate the need to supplement classical antibacterial therapy in eradication regimens with probiotics containing Lactobacillus acidophilus in order to increase the degree of eradication and reduce the incidence of side effects [45][46][47][48]. It is also shown that Lactobacillus acidophilus had an inhibitory effect on Hp in peptic ulcer patients and also in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we herein review the research progress made in H. pylori [ 20 ], S. pneumoniae [ 21 ], M.tb [ 22 ], and C. pneumoniae [ 23 ], which have been reported to be involved in lung cancer development and are not typically recognized as a subject in the research of the human microbiome and lung cancer, although H. pylori and S. pneumoniae are part of the commensal bacterial flora [ 56 , 57 ]. Consequently, this part of the review aims to inspire people to introduce the concept of biological pollutants in investigations of the microbiome and lung cancer, and to elucidate the relationship between biological hazards and human microbiota.…”
Section: Bacteria and Lung Cancermentioning
confidence: 99%
“…has been demonstrated to escape immunosurveillance mechanisms, thus allowing its long survival in the stomach. Furthermore, H. pylori is able to modify the gastric microbiota, thus causing a condition of dysbiosis, which may generate various diseases in addition to compromising human nutrition [12].…”
Section: Introductionmentioning
confidence: 99%